The Social Institutions and Gender Index (SIGI) 2019 A revised framework for better advocacy - Ferrant, Gaëlle (OECD Publishing, 2020)
Since 2009, the OECD Development Centre has been publishing the Social Institutions and Gender Index (SIGI), a cross-country measure of gender-based discrimination in social institutions (formal and informal laws, social norms and practices). This working paper presents the conceptual and methodological framework of the fourth edition of the SIGI, published in 2019. The SIGI 2019 methodology establishes a criterion for the computation of measures of gender-based discrimination -where zero denotes no discrimination and 100 denotes full discrimination - for 27 categorical and continuous variables combined into 16 indicators and 4 dimensions: discrimination in the family, restricted physical integrity, restricted access to productive and financial resources, and restricted civil liberties. The SIGI 2019 is then calculated as a translation-invariant generalised mean of these discrimination measures. The result is an indicator that measures aggregate level of discrimination in the social institutions of 180 countries and territories
Keywords: Development